(untitled) (Revista Cocar, 2023)
Pedagogical practices are situated activities that permeate the school context and concern the actions planned and executed by the teacher. Technologies have been of great value in streamlining these practices in this mediation process. Thus, this work aims to analyze the publications of the ANPEd, carried out from 2015 to 2021, about pedagogical practices using technologies. We adopted qualitative, through a review of the State of Knowledge literature, focusing on Work Group 4 – Didactics, and Work Group 16 – Education and Communication, based on the descriptors of pedagogical practice and technologies. The results indicate that few works deal with these descriptors interconnectedly in the time frame in question. In addition, the works do not present a clear concept of pedagogical practice(s). Therefore, investigations are needed to help elucidate this concept. Keywords: Pedagogical practices; Technologies; ANPEd. Resumo As práticas pedagógicas são atividades situadas que permeiam o contexto escolar e dizem respeito às ações planejadas e executadas pelo professor. Nesse processo de mediação, as tecnologias têm sido de grande valia para a dinamização dessas práticas. Assim, este trabalho objetiva analisar as publicações da ANPEd, realizadas de 2015 a 2021, acerca das práticas pedagógicas com a utilização de tecnologias. Adotamos a pesquisa qualitativa, através da revisão da literatura do tipo Estado do Conhecimento, tendo como foco o Grupo de Trabalho 4 – Didática, e o Grupo de Trabalho 16 – Educação e Comunicação, a partir dos descritores prática pedagógica e tecnologias. Os resultados apontam que, no marco temporal em questão, são escassos os trabalhos que versam sobre esses descritores de forma interligada. Além disso, os trabalhos não apresentam um conceito claro de prática(s) pedagógica(s), sendo necessárias, portanto, investigações que ajudem a elucidar esse conceito. Palavras-chave: Práticas Pedagógicas. Tecnologias. ANPEd.